Face Scanning in Autism Spectrum Disorder and Attention Deficit/Hyperactivity Disorder: Human Versus Dog Face Scanning - Muszkat, Mauro; de Mello, Claudia Berlim; Muñoz, Patricia de Oliveira Lima; Lucci, Tania Kiehl; David, Vinicius Frayze; Siqueira, José de Oliveira; Otta, Emma (Frontiers in Psychiatry, 2015)
This study used eye-tracking to explore attention allocation to human and dog faces in children and adolescents with autism spectrum disorder (ASD), attention deficit/hyperactivity disorder (ADHD), and typical development (TD). Significant differences were found among the three groups. TD participants looked longer at the eyes than ASD and ADHD ones, irrespective of the faces presented. In spite of this difference, groups were similar in that they looked more to the eyes than to the mouth areas of interest. The ADHD group gazed longer at the mouth region than the other groups. Furthermore, groups were also similar in that they looked more to the dog than to the human faces. The eye tracking technology proved to be useful for behavioral investigation in different neurodevelopmental disorders.